ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN PERSOALAN MATEMATIKA MATERI ALJABAR DENGAN KONTEKS NEW NORMAL - Adi Saputro; Zulkardi _; Ratu Ilma; Ely Susanti (Universitas Muhammadiyah Semarang, 2022)
This study aims to describe student errors in solving algebraic math problems in a new normal context. This research is a qualitative descriptive study. The subjects in this study were students of class VII A of SMPS Plus Lightning Literacy TP. 2021/2022. Test and interview methods were used as data collection methods. In order to obtain valid data, the researcher first checked the validity of the data using the time triangulation method. After obtaining valid data, the researcher analyzed the data and drew conclusions. From the results of the study, it was found that 1) Subject-A made 6 errors, namely: an error in writing a number symbol, an error in formulating an algebraic form, an error in simplifying, an error in carrying out the calculation process (determining the number of boxes) question number 2, an error in carrying out an operation division of integers (determining the number of boxes) question number 3, errors in the calculation process (determining the number of boxes) question number 4; 2) Subject-B made 3 mistakes, the errors were the same as subject-A, except for the error in writing the number symbol.